El ejercicio de la abogacía en España - Areta Martínez, María (Revista de Derecho, 2019)
The present work has as its objective to state the most significant changes that the practice of law has been experimenting in the 21st century as well as to discuss its challenges in a globalized society in constant evolution. In the last years, Spanish legal ordainment has experienced various reforms with the purpose of responding to needs posed in the practice of law now-a-days. Following, the author will cover all of these aspects.